2019
DOI: 10.1039/c9ra08936e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical looping hydrogen production with modified iron ore as oxygen carriers using biomass pyrolysis gas as fuel

Abstract: The chemical looping hydrogen (CLH) production was conducted in a fluidized bed reactor with the modified iron ore oxygen carriers (OCs) using simulated biomass pyrolysis gas (BPG) as fuel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Carbon capture efficiency (η c , %) η normalc = V CO 2 V CO 2 + V CO + V CH 4 × 100 % The theoretical hydrogen yield ( V normalH 2 * , mL) V normalH 2 * = ( V CO 0 V CO ) + ( V H 2 0 V H 2 ) + 4 × ( V CH 4 0 V CH 4 ) SR: …”
Section: Methodsmentioning
confidence: 99%
“…Carbon capture efficiency (η c , %) η normalc = V CO 2 V CO 2 + V CO + V CH 4 × 100 % The theoretical hydrogen yield ( V normalH 2 * , mL) V normalH 2 * = ( V CO 0 V CO ) + ( V H 2 0 V H 2 ) + 4 × ( V CH 4 0 V CH 4 ) SR: …”
Section: Methodsmentioning
confidence: 99%
“…The use of renewable reductants to produce green H2 has been already investigated by several authors. Xu et al [16] studied the feasibility to produce H2 from biomass pyrolysis gas in a fluidized bed reactor using modified iron ores as redox material. The results showed that the NiO-iron ore was the best material for hydrogen production leading to the highest hydrogen yields and purity (8.89 mmol/g and 99.02 %) with high cycle performance (10 consecutive cycles).…”
Section: Introductionmentioning
confidence: 99%